Probenecid‐Boosted Tenofovir: A Physiologically‐Based Pharmacokinetic Model‐Informed Strategy for On‐Demand HIV Preexposure Prophylaxis - Stephanie N. Liu; Zeruesenay Desta; Brandon T. Gufford (Wiley, 2020)
Multiple doses of tenofovir disoproxil fumarate (TDF) together with emtricitabine is effective for HIV preexposure prophylaxis (PrEP). TDF is converted to tenofovir (TFV) in circulation, which is subsequently cleared via tubular secretion by organic ion transporters (OATs; OAT1 and OAT3). Using in vitro kinetic parameters for TFV and the OAT1 and OAT3 inhibitor probenecid, a bottom‐up physiologically‐based pharmacokinetic model was successfully developed for the first time that accurately describes the probenecid-TFV interaction. This model predicted an increase in TFV plasma exposure by 60%, which was within 15% of the observed clinical pharmacokinetic data, and a threefold decrease in renal cells exposure following coadministration of a 600 mg TDF dose with 2 g probenecid. When compared with multiple‐dose regimens, a single‐dose probenecid‐boosted TDF regimen may be effective for HIV PrEP and improve adherence and safety by minimizing TFV‐induced nephrotoxicity by reducing TFV accumulation in renal cells.